2020
DOI: 10.1155/2020/8509650
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potential of Jatropha sp. Latex against Multidrug-Resistant Bacteria

Abstract: Objective. This study was aimed to evaluate the antibacterial activity of the latex of three species members of Jatropha (J. curcas, J. gossypilofia Linn., and J. multifida) against methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase- (ESBL-) producing Escherichia coli and ESBL-producing Klebsiella pneumonia, carbapenemase-resistant Enterobacteriaceae (CRE)-E. coli, K. pneumoniae-carbapenemase (KPC), and carbapenemase-resistant Pseudomonas aeruginosa (CRPA). Method. The antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
(12 reference statements)
0
23
0
1
Order By: Relevance
“…Methicillin-resistant Staphylococcus aureus (MRSA), extended spectrum beta-lactamase-producing Escherichia coli (ESBL-producing E. coli ) and the agar well diffusion method were used to evaluate the antibacterial activity of the isolated compounds [ 29 ]. The strains were cultured in nutrient broth at 37 °C for 18 h and diluted with steriled 0.9% NaCl to obtain the 1.5 × 10 8 CFU/mL bacterial solution.…”
Section: Methodsmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA), extended spectrum beta-lactamase-producing Escherichia coli (ESBL-producing E. coli ) and the agar well diffusion method were used to evaluate the antibacterial activity of the isolated compounds [ 29 ]. The strains were cultured in nutrient broth at 37 °C for 18 h and diluted with steriled 0.9% NaCl to obtain the 1.5 × 10 8 CFU/mL bacterial solution.…”
Section: Methodsmentioning
confidence: 99%
“…The MIC was determined as the lowest concentration of extract that completely inhibited the growth of the MRSA detected by the unaided eye (Valle et al 2015). MBC was defined as the concentration which exhibits zero growth of the colonies compared to the culture of the initial inoculum of the same strain (Manilal et al 2020;Prastiyanto et al 2020b). The Wells were subcultured using a 10 µL inoculating loop on to a BAP at (35 ± 2) o C for 16-20 h incubation.…”
Section: Minimum Inhibitory Concentrations (Mic) and Minimum Bactericmentioning
confidence: 99%
“…Infections caused by MRSA bacteria consume more health care resources than are consumed by patients infected with non-resistant strains of the same bacteria (Word Health Organization 2018). In consequence, novel antibacterial agents are needed from natural biological sources (Asagabaldan et al 2019;Lestari et al 2019;Prastiyanto et al 2020b;2020a, 2020c. Neutral proteoglycans derived from the P. ostreatus mycelia have been reported that could be used as immunomodulators and anticancer agents (Sarangi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of plants as medicine has been done since ancient times, (Al-dhabi and Arasu 2016; Elango et al 2016;Manh et al 2017). Many plants are used as traditional medicines having anticancer (Adnan and Ahmed 2019), antioxidant (Diniyah et al 2020), antibacterial (Prastiyanto et al 2020a;2020b) and antifungal (Kader et al 2011) properties. The members in Zingiberaceae have been recognized in uses of medicine such as antibacterial (Wibowo et al 2020), antifungal (Akter et al 2018), anticancer (Mahomoodally et al 2019), anti-arthritic (Murugesan et al 2020) and antioxidant (Ghafoor et al 2020).…”
Section: Introductionmentioning
confidence: 99%